The Impact Of Economic Contraction On The Financing Collectability Of Islamic Banking In Indonesia - Ernawati, Ernawati (JAS (Jurnal Akuntansi Syariah), 2024)
The COVID-19 pandemic affected Indonesia's economic growth, which experienced a contraction in the first and second quarters of 2020. This study examines how economic contraction affects the collectability of Islamic banking in Indonesia, period for 2019: IV - 2020: II. The measurement of financial collectability is based on non-performing financing (NPF). The research data source comes from secondary data in publications from the Central Statistics Agency (CSA) and the Financial Services Authority (FSA). Data analysis uses descriptive statistics with the help of percentages, growth, and graphs. The results indicated that the economic contraction significantly impacted the decline in Islamic banking performance, as evidenced by an increase in NPF. The NPF increase occurs in all debtor groups: MSMEs, non-MSMEs, and households (consumption financing). The collectability of financing is separate from the area where COVID-19 spreads; where DKI Jakarta, East Java, and West Java are in the top five highest COVID-19 cases, they have better financing collectability than other provinces. Based on economic sectors, only mining and quarrying did not experience an increase in the NPF during the economic contraction period. These findings show differences with the growth-led finance paradigm. Regions that experience high cases of COVID-19 infection have better financing collectability. The practical implication of these findings is the importance of coordinating macro prudential policies with others, such as fiscal and actual sector policy, in encouraging the resilience of MSMEs, including managing the collectability of financing during economic contraction periods.